Squamous cell carcinoma of the kidney: A case report - Lina, Juliana; Karo, Reh Malem br; Theresia, Yohani; Fadillah, Qori (Buletin Kedokteran & Kesehatan Prima, 2025)
Primary renal squamous cell carcinoma (SCC) is a rare neoplasm strongly associated with a history of nephrolithiasis. Renal SCC is reported to have high morbidity and mortality rates, especially in the elderly population. Clinical manifestations of renal SCC are generally characterized by hematuria, flank pain, and a palpable mass in the retroperitoneal area. Histopathological examination reveals the infiltration of squamous cell nests that destroy the stroma. These cells show nuclear pleomorphism, an increased nuclear/cytoplasmic ratio, irregular nuclear membranes, coarse chromatin, prominent and dense basophilic nucleoli, and eosinophilic cytoplasm. These histopathological findings confirm the diagnosis of squamous cell carcinoma. The uniqueness of this case lies in the diagnosis of renal SCC in a relatively young age group, making it a distinct clinical concern. Further immunohistochemical examination, including CK5/6, p63, p40, and CK14 panels, is needed to determine the prognosis and appropriate treatment strategy. This case report emphasizes the importance of understanding kidney stone disease as a preventive measure against the development of renal SCC.